Experimental assessment of a split air conditioner working with R-417A under different indoor and outdoor conditions. (January 2018) - Elgendy, E.; Melike, M.; Fatouh, M.
Highlights: Performance of R-417A in split air conditioner is experimentally investigated. R-417A has the same pressure levels, lower discharge temperature as compared with R-22. Cooling capacity and COP increase as the indoor air relative humidity increases. Compared to R-22, cooling capacity and COP decrease using R-417A. Abstract: The present paper aims to evaluate the performance characteristics of a split air conditioner working with R-417A under different indoor and outdoor operating conditions. A test facility was constructed and experiments were carried out to achieve the research objectives. The indoor conditions were varied in a wide range of air temperature (21–31.4 °C), air relative humidity (40.3%–61.9%) and air velocity (2.8–4.7 m s −1 ) while the outdoor conditions were changed in range of air temperature (35–51.2 °C) and air relative humidity (40.8%–81.2%). Experimental results showed that the increase in the indoor air temperature causes an enhancement in the system coefficient of performance by about 59.7%, while increasing the outdoor air temperature decreases the system coefficient of performance by about 51.6%. The system cooling capacity using R-417A was lower than that of R-22 by about 33.2% at indoor air temperature of 24.5 °C.